Factors affecting the prevalence of idiopathic scoliosis among children aged 8–15 years in Prishtina, Kosovo - Bernard Tahirbegolli (Nature Portfolio, 2021)
Abstract Prospective study, Level of evidence II. The aim of the study was to assess the prevalence of scoliosis among children aged 8–15 years old and to identify the impact of schoolbag weight in developing adolescent idiopathic scoliosis (AIS). AIS is a common disease whose prevalence varies between countries and gender, with an increased rate among females compared to males. Screening children in primary school settings for idiopathic scoliosis (IS) is an important public health issue and is crucial for early detection, prevention of further deformity, and healthy child growth. Our sample was composed of 1619 pupils from the municipality of Prishtina, surveyed from March to April 2019. Measurements were made with a scoliometer on the basis of the Adams test process. Three measurements were taken for each of the participants. Additionally, all the pupils were subjected to bare-foot height and weight measurements with and without school bags. The mean ± standard deviation age of pupils was 11.67 ± 2.00 years old and 49% were females. The prevalence of the angle of trunk rotation (ATR) ≥ 5 ° was 26.1%, females had 1.49 higher odds (95%CI 1.19–1.86) to develop an ATR of ≥ 5° compared to males. The highest rate of ATR of ≥ 5° was seen among the ninth-grade students (31.3%). 56.5% of 4th grade students carry a schoolbag weighing over 12.5% of body weight. Relatively high prevalence of idiopathic scoliosis was found in primary schools in Prishtina. The highest prevalence was found in students attending the ninth grade, while females gender dominated.